1994
DOI: 10.1093/oxfordjournals.humrep.a138752
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of interstitial pregnancy with methotrexate: report of an unsuccessful case

Abstract: Until now, the traditional management of interstitial pregnancy has been surgical. Lately, we have advocated conservative treatment with methotrexate as an option for infertility patients. This is the first publication of a rupture with abundant intra-abdominal bleeding during systemic treatment with methotrexate of a patient with an interstitial pregnancy. Signs of therapy failure are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…It is noteworthy that a regular decline in serum hCG levels is not always associated with the resolution of ectopic pregnancy. Rupture of the ectopic pregnancy can still occur, resulting in severe intra-abdominal haemorrhage, which is a life-threatening event, especially in interstitial pregnancy [23][24][25]. It has been a clinical experience that after application of methotrexate diffuse self-limiting abdominal pain can occur, imitating rupture of ectopic pregnancy [26].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that a regular decline in serum hCG levels is not always associated with the resolution of ectopic pregnancy. Rupture of the ectopic pregnancy can still occur, resulting in severe intra-abdominal haemorrhage, which is a life-threatening event, especially in interstitial pregnancy [23][24][25]. It has been a clinical experience that after application of methotrexate diffuse self-limiting abdominal pain can occur, imitating rupture of ectopic pregnancy [26].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment modalities range from conservative medical management to more invasive surgical techniques. The use of systemic methotrexate has been described in several case reports 3–5 and some larger series 6,7 . Local injection of methotrexate, potassium chloride or prostaglandin has also been described, either under ultrasound guidance or under direct vision by laparoscopy or hysteroscopy 2,6,8 .…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps we did not wait long enough for the ß-hCG to decrease after the local treatment. However, Voigt et al [35] stated that a slow decline in the ß-hCG concentration and a continuous growth of the CS during MTX treatment represent imminent signs of therapy failure. Hajenius et al [30] reported of eight interstitial pregnancies treated systemically with MTX (1 mg/kg i.m.…”
Section: Discussionmentioning
confidence: 99%